Tracking sesamin synthase gene expression through seed maturity in wild and cultivated sesame species – a domestication footprint. (9th April 2015) - Pathak, N.; Bhaduri, A.; Bhat, K.V.; Rai, A.K.; Bekker, R.
Abstract Sesamin and sesamolin are the major oil‐soluble lignans present in sesame seed, having a wide range of biological functions beneficial to human health. Understanding sesame domestication history using sesamin synthase gene expression could enable delineation of the sesame putative progenitor. This report examined the functional expression of sesamin synthase (CYP81Q1) during capsule maturation (0–40 days after flowering) in three wild Sesamum species and four sesame cultivars. Among the cultivated accessions, only S. indicum (CO‐1) exhibited transcript abundance of sesamin synthase along with high sesamin content similar to S. malabaricum, while the other cultivated sesame showed low expression. The sesamin synthase expression analysis, coupled with quantification of sesamin level, indicates that sesamin synthase was not positively favoured during domestication. The sesamin synthase expression pattern and lignan content, along with phylogenetic analysis suggested a close relationship of cultivated sesame and the wild species S. malabaricum. The high genetic identity between the two species S. indicum and S. malabaricum points towards the role of the putative progenitor S. malabaricum in sesame breeding programmes to broaden the genetic base of sesame cultivars. This study emphasises the need to investigate intraspecific and interspecific variation in the primary, secondary and tertiary gene pools to develop superior sesame genotypes.